Metastasis to the Bladder: A Rare Site of Recurrence of Renal Cell Carcinoma. (17th June 2022) - Smart, Amanda; Wynne, Michael; Baraban, Ezra; Ged, Yasser; Smith, Armine
Abstract : Renal cell carcinoma (RCC) is considered to be the deadliest urologic cancer with high rates of metastasis and recurrence after nephrectomy. RCC can metastasize to nearly any organ but most commonly metastasizes to the liver, lung, brain, and bone. To date, there are only about 40 reported cases of RCC with solitary bladder metastasis. The following report contributes to this limited data set of patients with RCC who develop solitary metastasis to the bladder. A 69-year-old male presented with occasional gross hematuria and was found to have a left renal mass infiltrating the collecting system. Ureteroscopic biopsy revealed clear cell RCC, and the patient subsequently underwent radical left nephrectomy. Eight months after nephrectomy, the patient presented to the clinic with gross hematuria. In-office cystoscopy demonstrated a nodular lesion in the bladder arising from the left ureteral orifice. The patient underwent transurethral resection of the bladder mass and pathology demonstrated clear cell RCC. Subsequent imaging showed no evidence of metastatic disease. Five months after transurethral resection, the patient was found to have a left distal ureteral mass and underwent left ureterectomy with partial cystectomy. Pathology again demonstrated clear cell RCC. RCC with solitary metastasis to the bladder is rare, and there are no targeted guideline recommendations for management. Per standard of care, patients with painless hematuria and risk factors for malignancy should undergo cystoscopy. In patients with a history of RCC, metastasis to the bladder should be considered in the differential diagnosis. Patients with metastatic RCC to the bladder should undergo a thorough work-up for additional sites of metastasis. In patients with RCC who develop solitary bladder metastasis amenable to resection following nephrectomy, there is a lack of evidence to guide therapy and a multidisciplinary discussion is warranted. However, if the tumor is amenable to resection, metastasectomy is a reasonable therapeutic approach and offers the patient an improved quality of life and an opportunity for remission.